Electrical conduction in the solid solution La1 -x Na x Co1 -x Nb x O3 (0·01 ≤x ≤ 0·99) - Parkash, O.M.; Kumar, D.; Kumar, R. (Springer India, 1988)
Scebeek coefficient and DC resistivity of the solid solution Lal _~Na~Col _~Nb~O3 (001 ~< x <~0-99) have been measured in the temperature range 300-900 K. Seebeck coefficient is positive for all compositionsover the temperature range of measurements. Conduction is due to 3d electrons of cobalt ions in the compositions with x~<0.60. Conduction occurs among localized sites for compositions with x >/0.70.
Keywords: Lanthanum cobaltate; lanthanum sodium cobalt niobium oxide; sodium niobate